Is Pesaḥ Passover? - Apple, Raymond (2018)
Although there is a scholarly dispute about the etymology of the verb p-s-h, this root is conventionally translated pass over: hence the English name Passover for the Hebrew term Pesah. This paper rejects this translation, which it believes is neither a good rendering of the Hebrew p-s-h nor an ac curate reflection of the way in which to pass over is used in modern English.